2018
DOI: 10.1002/jmv.25045
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum Golgi protein 73 for prominent hepatic necroinflammation in chronic HBV infection

Abstract: As a noninvasive marker, serum alanine aminotransferase (ALT) has limitations, because a large proportion of patients chronically infected with hepatitis B virus (HBV) suffer from severe hepatic necroinflammation, but have normal or mildly elevated ALT. In the present study, we aimed to investigate the potential value of serum Golgi protein 73 (GP73) in predicting significant hepatic necroinflamation among chronic HBV infected patients. A cohort of 497 chronic HBV infected patients was retrospectively recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
3
17
0
1
Order By: Relevance
“…Levels of serum GP73 rose in parallel with the severity of hepatitis and fibrosis, from nonexistent or mild to moderate and severe necroinflammation and fibrosis, even cirrhosis. These findings are similar to the recent reports demonstrating elevation of GP73 levels in HBV infection-related liver disease progression [2224, 31, 37, 38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Levels of serum GP73 rose in parallel with the severity of hepatitis and fibrosis, from nonexistent or mild to moderate and severe necroinflammation and fibrosis, even cirrhosis. These findings are similar to the recent reports demonstrating elevation of GP73 levels in HBV infection-related liver disease progression [2224, 31, 37, 38].…”
Section: Discussionsupporting
confidence: 92%
“…Though some studies have proven that serum GP73 was a valuable candidate for diagnosing advanced fibrosis and cirrhosis [21, 23, 38, 40] and may even have a higher diagnostic value compared to the traditional noninvasive indices such as APRI, FIB-4, and liver stiffness measurement (LSM) [21, 40], some other studies prefer it to be a new effective biomarker for diagnosing liver necroinflammation [22, 24, 37]. Noticeably, all these results are mainly from patients with HBV-related liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The NOS score of each study is presented in Supplementary Table 3 . Ten studies 5 , 6 , 8 , 24 , 30 , 31 , 33 , 34 , 38 were of high quality and 9 studies 7 , 25 29 , 32 , 35 37 were of moderate quality. There were no studies with low quality.…”
Section: Resultsmentioning
confidence: 99%
“…GP73 is upregulated in many chronic hepatopathies, including chronic viral hepatitis B and C, alcohol-related liver disease, and AIH [ 36 , 37 , 38 , 39 ]. Additionally, GP73 levels were considerably elevated in patients with significant necroinflammation, fibrosis, or cirrhosis [ 36 , 37 , 40 , 41 , 42 ], suggesting that GP73 could be used as a reliable surrogate marker for the detection of advanced fibrosis and cirrhosis but also for the monitoring of patients with liver diseases [ 16 , 37 , 40 , 43 , 44 , 45 ]. Indeed, recent reports have shown that serum GP73 is an accurate biomarker for the detection of significant fibrosis, bearing higher diagnostic accuracy than APRI and FIB-4 scores and that it could be used as a complementary tool to TE [ 20 , 46 ].…”
Section: Discussionmentioning
confidence: 99%